The Influence Of Motivation And Work Environment On Employee Performance With Job Satisfaction Chandra Department Store Bandar Lampung - Alma Salsabila; Alridha Triandita Sagita; M. Fakhri Ikramsyah; Febrianty Febrianty; Reza Hardian Pratama (Journal of Innovative and Creativity (Joecy), 2026)
This study is based on improving employee productivity in the highly competitive retail industry, focusing on examining the influence of motivation and work environment on the continuity of employee performance, conducted directly or indirectly by applying job satisfaction to employees at Chandra Department Store in Bandar Lampung. This study applies a quantitative method by distributing questionnaires to 100 respondents selected based on criteria, as well as applying Structural Equation Modeling analysis based on Partial Least Squares (SEM-PLS), The research findings show that motivation as a positive contribution to improving employee performance, and the work environment significantly influences job satisfaction. However, motivation does not show a significant contribution to job satisfaction, and the work environment does not directly influence job satisfaction. In addition, job satisfaction shows a mediating role in the effect of the work environment on performance continuity, but it does not mediate the influence of motivation on performance continuity. The conclusion of this study proves that improving employee performance is more effective by directly strengthening work motivation and optimizing job satisfaction as a mediator of the work environment, providing contributions to the advancement of human resource management theory, including presenting practical implications for employee management in the retail sector.